Factors influencing the scientific production of university professors: A systematic review (2018)
This article presents a bibliographical review of empirical studies of the factors influencing the scientific production of professors, with the objective of characterizing scientific production in the university and its determining factors. It was carried out through the analysis of articles that present the situation of institutions of higher education. To find these articles, search strings were used in various databases, including Scopus, Scielo, Taylor and Francis, and inclusive and exclusive terms were used to delimit the articles found. An analysis is provided of the factors influencing scientific production, based on type of institution training and professional development, as indicators of their essential characteristics.